Berbagai Tumbuhan Obat Tradisional Di Asia Dengan Aktivitas Antiasma - Nabila Nayif Nur Akmalia (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2020)
Natural ingredients are a good source of active compounds and drugs. The study of plant content is very interesting in the discovery of active compounds, especially for therapy in asthma. Asthma is a chronic disease with symptoms of wheezing, shortness of breath, chest tightness, and coughing. There are several mechanisms of action of anti-asthma compounds related to the types of asthma, namely H1 and H2 receptor inhibitors, reducing immunoglobin E levels, inflammation mediators, preventing secretion of cytokine Th2, and other specific mechanisms. The method used is literature study. The study was conducted by searching keywords such as herbs, anti-asthma, medicinal plants, and anti-asthmatic activity on electronic databases including ClinicalKey, Science Direct, PubMed, and Google Scholar. Therefore, data and explanations about potential medicinal plants found throughout Asia as alternative sources of asthma treatment were obtained.Thirty types of traditional medicinal plants in Asia that have the anti-asthma activity potential to have been obtained by various mechanisms of action. The plants activity data collected in this literature review indicate their use as an alternative source of asthma treatment.